Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal - Ng, Heok Hee; Edds, David R. (Zootaxa, 2005)
Two new species of sisorid catfish of the genus Pseudecheneis are described from tributaries of the Ganges River in Nepal: Pseudecheneis crassicauda and P. serracula. Pseudecheneis crassicauda can be distinguished from congeners by a unique combination of 38–39 vertebrae, caudal peduncle depth 6.0–6.6% SL, eye diameter 7.5–8.3% HL, length of adipose-fin base 20.3–24.3% SL, pelvic fins reaching the base of the first anal-fin ray, and the presence of pale spots on the body. Pseudecheneis serracula can be distinguished from congeners in having a unique combination of 36–38 vertebrae, strongly elevated neural spines of the last 2–3 preanal and first 6–7 postanal vertebrae, length of adipose-fin base 26.8–30.4% SL, pelvic fins reaching the base of the first analfin ray, and the presence of pale spots on the body.